A NATUREZA DO OBJETO NULO E DO NOME NULO NO PORTUGUÊS EUROPEU - Kato, Mary (2012)
This paper brings a discussion on Raposo’s ideas about the null object and the null article in Romance, to show that, though the two varieties of Portuguese are closer than the other Romance languages, these aspects still distinguish the two grammars when the spoken variety of Brazilian Portuguese is taken into account.